Super Fair Dominating Set in the Cartesian Product of Graphs - Glenna T. Gemina; Enrico L. Enriquez (International Journal of Engineering and Management Research, 2020)
In this paper, we characterize the super fair dominating set in the Cartesian product of two graphs and give some important results.